Chronicle - RUTSTR ÖM, EDVARD; WICKERSTR ÖM, JONAS (My University, 2013)
Many games of high complexity give rise to emergent narratives, where the events of the game are retold as a story. The goal of this thesis was to investigate ways to support the player in discovering their own emergent stories in grand strategy games. Grand strategy games are games of high complexity, and player communities based on these games are very focused on sharing stories spawned from the games. The focus of this thesis has been on collecting these stories and showing them, not creating new stories by changing the gameplay rules. The area was explored by developing a digital prototype that was tested on users. The prototype is a chronicle for the game Crusader Kings II, which collects events that happen in the game and show them as icons and ags on a timeline. The development leading up to the prototype and nal concept included literary studies, interviews, questionnaires, persona development, and paper prototyping. The aim of this thesis was to give users an easy way to see their story more clearly. By using the familiar concept of a timeline, users can see what they have accomplished, and get a reminder when they return to a game after a long time.
Keywords: Interaktionsteknik; Interaction Technologies